The Routledge handbook of religion and journalism - Radde-Antweiler, Kerstin; Zeiler, Xenia (Routledge handbooks in religion, 2021)
"The Routledge Handbook of Religion and Journalism is an outstanding reference source to the key topics, challenges, past and present global issues, and debates in this exciting subject. The first collection of its kind, this volume comprises over 25 chapters by a team of international contributors. The Handbook is divided into five parts, each taking global developments in the field into account: Theoretical Reflections Power and Authority Conflict, Radicalization and Populism Dialogue and Peacebuilding Trends Within these sections, central issues, debates and developments are examined, including: Religious and secular press; ethics; globalization; gender; datafication; differentiation; journalistic religious literacy; race, and religious extremism. This volume is essential reading for students and researchers in journalism and religious studies. The Handbook will also be very useful for those in related fields, such as sociology, communication studies, media studies and area studies"